Tetrakis(mu(2)-2,2-dimethylpropanoato-kappa O-2,O `)bis[(pyridine-kappa N)copper(II)]: A monoclinic polymorph - Ozair, L.N.; Abdullah, N.; Khaledi, H.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The structure of the dinuclear title complex, [Cu-2(C5H9O2)(4)(C5H5N)(2)], represents a monoclinic polymorph of the previously reported triclinic form [Blewett et al. (2006). Acta Cryst. E62, m420-m422]. Each carboxylate group is bidentate bridging and the distorted octahedral geometry about each Cu II atom is completed by a pyridine N atom and the other Cu atom [Cu center dot center dot center dot Cu = 2.6139 (7) angstrom]. In the crystal, molecules are connected into supramolecular chains via pi-pi interactions formed by the pyridine rings [centroid-centroid distance = 3.552 (3) angstrom] and these are connected into a two-dimensional array in the ac plane by C-H center dot center dot center dot pi contacts. One of the tertbutyl groups is disordered over two orientations in a 0.734 (6): 0.266 (6) ratio.